Corrosion behavior of austenitic chromium-manganese stainless steels in citric acid - Mulimbayan, Francis M.
Stainless steel (SS) may be classified according to its microstructure - ferritic, austenitic, martensitic, duplex, and precipitation hardening grades. Among these, austenitic grades have the largest contributioon to market due to the alloy's numerous industrial and domestic applications. An electrochemical study was performed on AISI 202 SS - a low-Ni austenitic, Cr-Mn SS, in order to evaluate its corrosion behavior in citric acid subjected to different concentrations (50, 100 and 150 g/L), temperatures (23±0.5, 50 and 70°C) and dissolved O2 (low and high level). The conventional AISI 304 SS was also studied for comparative purposes. Electrochemical techniques such as Open Circuit Potential (OCP) measurements, Potentiodynamic Polarization and Electrochemical Impedance Spectroscopy (EIS) were used to extract information regarding the stability, corrosion rate, susceptibility to pitting and corrosion mechanisms of the studied alloy in the designated environment. OCP, polarization and impedance measurements revealed that in general, corrosion behavior of AISI 202 SS did not vary much within the studied range of concentration. On the contrary, the corrosion behavior of the studied alloy exhibited a marked dependence on citric acid temperature. Raising citric acid temperature shifted OCP and corrosion potential (Ecorr) to more negative values and resulted to lower polarization resistances (Rp) and higher corrosion current densities (icorr) and higher cathodic Tafel slopes (bc), indicating that the alloy corroded faster and became less stable at elevated citric acid temperatures. Increasing the amount of dissolved O2 consequently increased teh Rp and shifted the OCP to more positive values, which implies greated stability of the studied alloy in solution with high dissolved O2. However, all the polarization-related parameters, in general, showed no dependence on the dissolved O2 level. Corrosion of the alloy in all the studied citric acid temperatures and at any dissolved O2 level is activation-controlled as indicated by the generated Nyquist plots appearing as on or two depressed capacitive loops. The equivalent circuit (EC) model of the alloy interface at 23±0.5°C approximates that of a passivated surface while at 50 and 70°C, the corresponding EC model is that of a film composed of two porous layers. At high level of dissolved O2, the EC model of the interface is that of a film with single porous layer. At 23±0.5°C up to 50°C, AISI 202 SS exhibited similar corrosion behavior to the conventional AISI 304 SS in citric acid as indicated by comparable values of measured OCP, Ecorr, icorr, bc, and Rp. At 70°C however, results of potentiodynamic polarization and OCP measurements both suggest that AISI 304 SS exhibited greater performance in terms of corrosion resistance than AISI 202 SS. The values of icorr and bc extracted from polarization curves indicate that the initial corrosion rates were higher in AISI 304 SS suggesting that faster formation of film which is more protective occured on the surface of this alloy. Cyclic voltammetry (CV) scan in any studied concentrations at 23±0.5°C showed no hysteresis loops indicating that the two alloys are highly resistant to pitting in the designated solution. Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray (EDX) and X-Ray Diffraction (XRD) analyses were performed to characterize the passivation layer formed on the alloy surface after polarization. No signs of pitting were detected on the surface. The passivation film formed on the surface of polarized AISI 202 and AISI 304 SS exposed to citric acid of any concentration, temperature or dissolved O2 level is composed mainly of oxides of Fe, Cr